Steroid reference intervals in women: influence of menopause, age and metabolism. Issue 3 (March 2021) - Mezzullo, Marco; Gambineri, Alessandra; Di Dalmazi, Guido; Fazzini, Alessia; Magagnoli, Matteo; Baccini, Margherita; Vicennati, Valentina; Pelusi, Carla; Pagotto, Uberto; Fanelli, Flaminia
Abstract : Objective: To investigate the impact of age, obesity and metabolic parameters on 13 circulating steroids in reproductive and menopausal age. To define reference intervals (RIs). Design: Cross-sectional. Methods: Three hundred and twenty five drug-free, healthy and eumenorrheic women were selected from the general population. Independent relationships of LC-MS/MS-determined steroid levels with age, BMI and metabolic parameters were estimated. Reference sub-cohorts were defined for calculating upper and lower limits in reproductive age, menstrual phases and menopause, and these were compared with limits in dysmetabolic sub-cohorts. Results: Lower androgens, pro-androgens and estrogens, but higher cortisol and metabolites were found in menopausal compared to reproductive age women. Androgens and precursors decreased during reproductive age ( P < 0.001 –P = 0.002) but not after menopause. 17OH-progesterone decreased with BMI ( P = 0.006) and glucocorticoids with waist circumference ( P < 0.001 P = 0.002) in reproductive age, but increased with triglycerides ( P =0.011 P =0.038) after menopause. Inverse associations of dihydrotestosterone with BMI ( P =0.004) and HDL-cholesterol ( P =0.010), estrone with total cholesterol ( P =0.033) and estradiol with triglycerides ( P =0.011) were found in reproductive age. After menopause, estrone increased with waist circumference ( P <0.001) and decreased with insulin resistance ( P =0.012). Ovarian steroid RIs were estimated in menstrual phases and menopause. Age- and reproductive status-specific RIs were generated for androgens, precursors and corticosteroids. Lower limits for reproductive age cortisol ( P =0.020) and menopausal 11-deoxycortisol ( P =0.003) in dysmetabolic sub-cohorts were reduced and increased, respectively, compared to reference limits. Conclusions: Obesity and dysmetabolism differently influence circulating steroids in reproductive and menopausal status. Age, menstrual and menopausal status-specific RIs were provided by LC-MS/MS for a broad steroid panel.